Sounds of attraction : Yugoslav and post-Yugoslav popular music - Kozorog, Miha; Muršič, Rajko (Zbirka Zupaničeva knjižnica ;, 2017)
"Popular music in former Yugoslavia appear to have had a much deeper impact on the development of the socialist state and its successors than is usually thought to be the case. The collection by the authors from the region presents feelings, stories and memories on popular music in Yugoslavia and its successor states."